Alien Eyes on Human Faith: A Critical Reading of Rajkumar Hirani’s PK - Rehan Aslam Sahi; Mudassar Ali (Journal of Religion and Society, 2025)
PK by Rajkumar Hirani (2014) is not a simple Bollywood movie, it is a profound social satire, in which the author uses the alien stranger archetype to demonstrate the hypocrisy and absurdity of human life. In the character of PK who is played by Aamir Khan, the movie discloses the unstable pillars of trust, identity and cultural practice in the contemporary Indian society. This abstract brings PK to the level of being more than a visitor to this earth, he is more a mirror of contradictions of what human beings preach and what they actually project. Making himself innocent, honest and naive, PK disturbs what the society usually regards as the unquestionable truth, particularly the truth about the faith, social conventions, and inter human relationships. The significance of the outsider perspective in the film is that it has made the use of estrangement as a narrative element. The misconception of PK regarding the language, dress, rites, and gods emphasizes the extent to which the human culture is artificial instead of natural. The practices that have been naturalized over centuries are broken down by his constant questioning, which may seem childish. Through this, the character of PK makes the audience question the difference in the ideals and the twisted institutionalization of spirituality.Through the depiction of the alien as the most humane character in the film, the movie dismantles strict dichotomies, including self and other, believer and non-believer, and human and alien. This paper suggests that PK is a cultural critic whose naivety is his subversive weapon of choice. Although people in the movie are caught in the web of exploitation, manipulation, and blindness, the outsider position of PK provides him with the clear mind to reveal the absurdities without biases. His constant question, which is the wrong number, turns out to be a metaphor of miscommunication between humans and divine, as well as between people themselves. Moreover, being an alien makes him a complexity to the traditional identity politics: he is everywhere and nowhere at the same time, which enables him to point out the absurdity of the strict social terms and the universal necessity to lend a shoulder to lean on. Through the examination of PK as an outsider who redefines the definition of being human, this paper illustrates how the movie employs satire and humor to question some of the social practices entrenched in people. It places PK into a greater context of outsider characters in literature and movies who serve a truth-telling purpose precisely due to the fact that they do not follow the norms of the societies they are witnessing. In the end, the character of PK turns out to be the means of revealing the fact that the contradictions that humans are afraid to address is the most evident when we view them through the lens of the other. By so doing, not only does the film entertain, but it as well forces viewers to reflect on whether their lives are based on moral and cultural grounds. Keywords: Alien Eyes, Human Faith, Rajkumar Hirani’s PK, Truth-Telling, Cultural Grounds. https://doi.org/10.5281/zenodo.17259306